Publishing Greek and Latin Classics in 19th-century Milan: Giovanni Silvestri and the «Biblioteca scelta di opere greche e latine tradotte in lingua italiana» (1820-1855) (Prassi Ecdotiche della Modernità Letteraria, 2022)
This article investigates the cultural guidelines that inspired the creation of the Biblioteca scelta di opere greche e latine tradotte in lingua italiana, a book series of Italian translations of Greek and Latin works - mostly Classics - published by the Milanese publisher Giovanni Silvestri between 1820 and 1855. A list of the titles contained in the series is provided in the Appendix.
Keywords: Giovanni Silvestri; Milanese publishing industry; Italian vernacular translations; Biblioteca scelta